2012
DOI: 10.1038/ki.2011.505
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone blockade and the mineralocorticoid receptor in the management of chronic kidney disease: current concepts and emerging treatment paradigms

Abstract: The past two decades have witnessed a striking paradigm shift with respect to our understanding of the widespread effects of aldosterone. There is substantive evidence that mineralocorticoid receptor (MR) activation promotes myriad 'off target' effects on the heart, the vasculature, and importantly the kidney. In the present review, we summarize the expanding role of MR activation in promoting both vascular and renal injury. We review the recent clinical studies that investigated the efficacy of MR antagonism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 84 publications
1
68
0
2
Order By: Relevance
“…This approach may have less effect on reducing glomerular capillary pressure, but aldosterone antagonists are potent antifibrotic agents. Recent data have shown that aldosterone is positioned upstream of multiple profibrotic pathways and that angiotensin 2 is only one of many stimuli to aldosterone production (131). This combination confers a risk for hyperkalemia, particularly with reduced GFR; this may be controlled with dietary restriction and diuretics, although close monitoring may be required.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…This approach may have less effect on reducing glomerular capillary pressure, but aldosterone antagonists are potent antifibrotic agents. Recent data have shown that aldosterone is positioned upstream of multiple profibrotic pathways and that angiotensin 2 is only one of many stimuli to aldosterone production (131). This combination confers a risk for hyperkalemia, particularly with reduced GFR; this may be controlled with dietary restriction and diuretics, although close monitoring may be required.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…2 While treatment with MRA might be thought to be of limited efficacy in patients on ACEi or ARB therapy, detailed study of patients on this treatment reveals that in many cases use of ACEi and ARB decreases levels of circulating aldosterone only for a period of weeks. In 10-50% of patients' circulating aldosterone concentrations return to pre-treatment levels (a phenomenon termed 'aldosterone breakthrough').…”
Section: Discussionmentioning
confidence: 99%
“…4 Strong evidence suggests that ACEi and ARB drugs do not effectively inhibit aldosterone production in all patients and that aldosterone may also be a mediator of renal and cardiovascular damage in patients with CKD. 2 Mineralocorticoid receptors are present in the brain, heart and blood vessels as well as the kidney, and there is evidence of aldosterone production within these tissues. 5 Local mineralocorticoid receptor activation by aldosterone causes numerous pathological effects on the cardiovascular system including endothelial injury, inflammation, oxidative stress and fibrosis in the heart and vasculature, as well as the development of hypertension and autonomic dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Studies over the past two decades have shown that aldosterone plays an independent role as a mediator of kidney injury and progression of chronic kidney disease. 29 Aldosterone has been shown to exert its effects through genomic or non-genomic pathway. 30 Genomic effects of aldosterone are generally thought to be mediated by the MR and involve transcription, while aldosterone can also exert rapid nongenomic effects that are not blocked by inhibitors of transcription.…”
Section: Discussionmentioning
confidence: 99%